Ionic liquids under nanoscale confinement. Issue 1 (1st January 2020) - Borghi, Francesca; Podestà, Alessandro
ABSTRACT: The confinement of room-temperature ionic liquids (ILs) in nanoscale geometries, where at least one, but often all three dimensions are reduced down to lengths comparable to the anion-cation size, put the ILs into a quite different condition with respect to their bulk phase. An understanding of the properties of the ILs conﬁned in a nanoscale-constrained geometry is of both fundamental and practical interest. In particular, the spatial restriction of ILs promotes a strong interaction of the ILs with the surface of the conﬁning matrix, which strongly affects their properties, like the phase transition behavior, layering near surface walls, wetting, as well as ionic mobility. This short review is especially concerned with the interfacial confinement of ILs on solid substrates, in the form of very thin films, or inside porous nanomaterials. Graphical Abstract: